THE USE OF SNS AMONG THE UNDER GRADUATE STUDENTS OF ASAS KOCHI - Darshan B.M and Sai C.S (International Education & Research Journal, 2016)
Communication has been instrumental to a large extent in the growth of Social Networking Sites (SNS). With the advent of Internet and the cell phone a lot of social interaction is captured through email and instant messaging. Today there are a lot of online social networking sites where individuals volunteer information about them- selves and their social networks. Social networking allows for like- minded people to interact with another. An online social networking site is a place where a user can create a profile and build a personal network that connects the user to other users. Teenagers and young adults are fanatic users of these sites. According to various research studies in the field of online social networks, it has been revealed that these sites are impacting the lives of the youth greatly. This study is to understand the extent to which the under-graduate students use social networking sites as well as their attitudes to this form of communication. This research is based on survey method and this study is conducted on a sample of 50 students studying in various disciplines of Amrita School of Arts and Sciences (ASAS) Kochi campus. The main objective of this study is to understand why students use social networking sites, to what extent social networking sites are affecting on their studies, to analyse whether the students trust the information obtained via social networking sites and to explore the impact of SNS on students.